Don’t forget the porpoise: acoustic monitoring reveals fine scale temporal variation between bottlenose dolphin and harbour porpoise in Cardigan Bay SAC - Hanna Nuuttila (Marine Biology, 2017)
Populations of bottlenose dolphin and harbour porpoise inhabit Cardigan Bay, which was designated a Special Area of Conservation (SAC), with bottlenose dolphin listed as a primary feature for its conservation status. Understanding the abundance, distribution and habitat use of species is fundamental for conservation and the implementation of management. Bottlenose dolphin and harbour porpoise usage of feeding sites within Cardigan Bay SAC was examined using passive acoustic monitoring. Acoustic detections recorded with calibrated T-PODs (acoustic data loggers) indicated harbour porpoise to be present year round and in greater relative abundance than bottlenose dolphin. Fine-scale temporal partitioning between the species occurred at three levels: (1) seasonal differences, consistent between years, with porpoise detections peaking in winter months and dolphin detections in summer months; (2) diel variation, consistent across sites, seasons and years, with porpoise detections highest at night and dolphin detections highest shortly after sunrise; and (3) tidal variation was observed with peak dolphin detections occurring during ebb at the middle of the tidal cycle and before low tide, whereas harbour porpoise detections were highest at slack water, during and after high water with a secondary peak recorded during and after low water. General Additive Models (GAMs) were applied to better understand the effects of each covariate. The reported abundance and distribution of the two species, along with the temporal variation observed, have implications for the design and management of protected areas. Currently, in the UK, no SACs have been formally designated for harbour porpoise while three exist for bottlenose dolphins. Here, we demonstrate a need for increased protection and species-specific mitigation measures for harbour porpoise.